“Estudio de tiempos y movimientos para la optimización de la producción en la empresa Textiles Cotopaxi”. - Llano Llano, Iván Elvis (2021)
The present investigative work, which was carried out in the Cotopaxi Textile Company, which is dedicated to the dyeing of fabrics. The main objective was to carry out a study of times and movements for the optimization of the production that is carried out on a daily basis in that place. In addition, it was found that they did not have real knowledge of the time and the activities to be carried out in the dyeing area, for which they used more than 8 hours for the fulfillment of a production cycle, in addition, dead times were observed between the activities that It is developed for the dyeing of fabrics and the lack of a standard time in the performance of the different tasks that are carried out by the manipulation of the operators to the machines, therefore, the problem influences the effectiveness and efficiency of the tasks of accomplishment, and in the level of productivity expected in a normal day of work that would be in its 8 hours. It is worth mentioning that research techniques such as observation were applied, oriented to the analysis of each of the tasks that are gradually carried out for the fulfillment of the fabric dyeing process, taking into account the following activities: assembly of the fabric, verification of the control panel, putting the chemicals, verification and other tasks so it was indicated that these times had to be improved to improve the production rate and increase the performance in the area.